Comparison of dobutamine stress echocardiography with dipyridamole stress echocardiography for detection of viable myocardium after myocardial infarction treated with thrombolysis. - Poli, A. (1996)
OBJECTIVE: To compare the ability of dobutamine and dipyridamole stress echocardiography to detect functional recovery of stunned but viable myocardial regions early after acute myocardial infarction, and to predict late functional recovery of the reperfusion salvaged myocardium within the infarct area. METHODS: Within 10 d of acute myocardial infarction, 51 patients--30 anterior and 21 inferior, 44 Q wave and seven non-Q-wave infarction--were submitted to a dobutamine echocardiography test at low dose (5-10 micrograms/kg/min over 5 min) and high dose (20-40 micrograms/kg/min over 3 min) and to dipyridamole echocardiography test (0.56 mg/kg over 4 min + 0.28 mg/kg over 2 min) on different days and in random order, after interruption of any vasoactive drug. Resting echocardiography was repeated at two months in 41 of 51 patients (80%). Regional wall motion of the left ventricle was analysed in a semiquantitative manner on a 14-segment model. Viability was defined as improvement of one grade or more of at least two basally asynergic segments in the infarcted area. RESULTS: Regional functional recovery was detected by low dose dobutamine in 38/51 patients (75%) and in 147/308 (48%) of basally asynergic segments, compared to 25/51 patients (49%; P < 0.001) and 78/308 segments (25%; P < 0.001) only identified by dipyridamole. Late spontaneous functional recovery was detected in 24/41 patients (59%) and in 78/254 basally asynergic segments (31%). The sensitivity of dobutamine and dipyridamole echocardiography for predicting spontaneous functional recovery was 72% and 51% respectively (P < 0.001), specificity 68% and 82% (P < 0.001), positive predictive value 50% and 56%, and negative predictive value 85% and 79%. CONCLUSIONS: In comparison with dipyridamole in patients with thrombolysed myocardial infarction, dobutamine induces regional functional recovery. This suggests that dobutamine is more sensitive in showing the presence of viable myocardium within the infarct zone, though it has a lower specificity in predicting delayed spontaneous functional recovery of non-contractile but still viable areas.